The Christian Entrepreneur: Dream, Plan, Execute, Grow. - Shinen, Brock (Bethany House Publishers, 2020)
The road to launching a successful business can be long and confusing. This step-by-step guide from legal expert and business coach Brock Shinen combines practical wisdom and a biblical worldview to help you turn your dreams and passions into a viable business. Be inspired as The Christian Entrepreneur helps you through every stage of your journey!.